2018
DOI: 10.1111/liv.13952
|View full text |Cite
|
Sign up to set email alerts
|

The influence of drug properties and host factors on delayed onset of symptoms in drug‐induced liver injury

Abstract: This study demonstrated that delayed onset, a specific DILI phenotype, is explained by complex interactions among drug properties and host factors and provided mechanistic hypotheses for future studies. These findings can help improve the diagnostic capability and causality assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…In addition, some of these studies considered elevated liver biochemistries at 6 months as chronic or persistent DILI; others considered that time to be at 12 months. Besides clinical factors, drug factors such as lipophilicity, dose, and metabolism can also influence DILI phenotypes 30,31 or DILI risk. 13,15,32,33 In this study, we found that the extent of hepatic metabolism of offending drugs was significantly associated with recovery time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some of these studies considered elevated liver biochemistries at 6 months as chronic or persistent DILI; others considered that time to be at 12 months. Besides clinical factors, drug factors such as lipophilicity, dose, and metabolism can also influence DILI phenotypes 30,31 or DILI risk. 13,15,32,33 In this study, we found that the extent of hepatic metabolism of offending drugs was significantly associated with recovery time.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study, the incidence of DILI is approximately 2.7 cases of DILI per 100 000 adults, and because the prevalence of DILI is quite low, the sample size was insufficient to determine the frequency of DILI development in a clinical trial . Furthermore, the universal risk factor for DILI remains unclear, although genetic risk might be associated with DILI . Several studies suggested that the pathophysiology of DILI might be multifactorial; thus, establishing an examination with high sensitivity for prediction of idiosyncratic DILI is difficult .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the threshold dose may have substantial inter-individual variability (DILI may occur when increasing the dose, still within the recommended daily dose range) (Carrascosa et al, 2015), and DILI induced by agents used at daily dose higher than 50 mg was found to have significantly shorter latency period as compared with DILI caused by drugs taken at lower dosage (38 vs 56 days) (Vuppalanchi et al, 2014). Antibiotics are an exception: amoxicillin-clavulanate (daily dose >1000 mg) was associated with a particular phenotype of “delayed onset of DILI,” a term referring to the delay in DILI manifestations after interruption of the agent, to be distinguished from long latency time during drug administration (Gonzalez-Jimenez et al, 2019). Therefore, the question arises as to whether or not high dose is just an epiphenomenon, and DILI simply overlaps with most frequently prescribed medications used at recommended doses.…”
Section: Etiology Of Dili: the Role Of Drug Propertiesmentioning
confidence: 99%